MiR‑222-3p reduces neuronal cell apoptosis and alleviates spinal cord injury by inhibiting Bbc3 and Bim. (March 2023) - Zhang, Qiangqiang; Li, Gang; Kong, Jundong; Dai, Junyu; Fan, Zhongkai; Li, Jian
Abstract: Spinal cord injury (SCI) is a severe traumatic event, but without any established effective treatment because of the irreversible neuronal death. Here, we investigated the role of miR-222-3p in neuronal apoptosis following SCI. Rat SCI models and neuron hypoxia models were accordingly established. The Bbc3, Bim, Bcl-2, Bax, cleaved-caspase 3, cleaved-caspase 9, Cytochrome c, and miR-222-3p expression levels were examined by Western blotting and real-time reverse transcription polymerase chain reaction (RT-qPCR). The possible association between miR-222-3p and Bbc3/Bim was analyzed by dual-luciferase assay. The neuron viability was assessed by Cell Counting Kit-8 assay and Nissl's staining. Live cell staining was performed to detect the mitochondrial membrane potential and neuronal apoptosis. Rat locomotor function was assessed using the Basso–Beattie–Bresnahan scores. Cytochrome c was outflowed from the mitochondria after SCI or hypoxia treatment, and Bbc3, Bim, Bax, cleaved-caspase 9, and cleaved-caspase 3 were significantly upregulated, while Bcl-2 and miR-222-3p were decreased remarkably. Meanwhile, neuronal cell viability was significantly inhibited. Treatment of miR-222-3p significantly suppressed the Cytochrome c efflux and neuronal apoptosis and improved neuronal cell viability and motor function in SCI rats. Moreover, we found that Bbc3 and Bim were the direct targets of miR-222-3p. Overall, our data suggest that miR-222-3p could alleviate the mitochondrial pathway-mediated apoptosis and motor dysfunction in rats after SCI by targeting Bbc3 and Bim. Highlights: Massive neuronal apoptosis is the main cause of dysfunction after SCI. The Bbc3, Bim and miR-222-3p were played an important role in neuronal apoptosis after SCI. miR-222-3p can directly inhibit the expression of Bbc3 and Bim. Increasing miR-222-3p after SCI can inhibit neuronal apoptosis and promote functional recovery.